PENGARUH IMPLEMENTASI MEDIA VIDEO PEMBELAJARAN TERHADAP MINAT BELAJAR IPA PESERTA DIDIK KELAS IV SDN SUKAKARYA 2 - Denni, Irdam; Taofik, De Budi Irwan; Susila, Aceng Ahmad Rodian; Nugraha, Widdy Sukma (IPI Press, 2024)
This research aims to determine the increase in students' interest in learning in science subjects through the use of learning video media. The method used is an experimental method using a quantitative approach. The form of experimental method used is Pre-Experimental Design. The form of experimental design used in this research is one group pretest-posttest design. The sample used in this research was one class IV with a total of 21 students. The sampling technique used was nonprobability sampling with the technique taken being saturated sampling. The data collection technique uses an observation sheet instrument. Data analysis used descriptive statistics, N-Gain, and the Wilxocon test. The research results can be concluded that the application of learning video media can increase students' interest in learning in Natural Sciences subjects, this is in accordance with the research results where the average learning interest of students before and after the application of learning videos was 23.76 and 36 respectively. .00, and an average increase of 0.5014 is included in the medium category